KONSTRUKSI HUKUM PROGRESIF; URGENSINYA DALAM PENYELESAIAN SENGKETA EKONOMI SYARI’AH - Salasti Faridatun Hasanah; A. Kumedi Ja’far; M. Iqbal Fasa (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
Dutch colonialism made Indonesia embrace the legal positivism system. Legal positivism views the law as a a fixed, logical and closed system. The written law is so exalted and does not allow contextual interpretation. The truth that is believed is the truth that can be proven (pragmatic). Along with the development of the era, which is marked by the increasingly complex problems that arise, including sharia economics, it cannot be solved with a positivistic paradigm. The law must develop along with the development of problems in society in order to create the ideals of justice. with similar thought, satjipto rahardjo then sparked his progressive legal concept which places humans and humanity as the main discourse or primus in the discussion and enforcement of law and formulated an adagium